Pengaruh Senam Otak Terhadap Fungsi Kognitif Dengan Demensia Pada Lansia Di Dusun Karang Kecamatan Kualuh Hulu Kabupaten Labuhan Batu Utara Tahun 2022 - Ade Aulia Siahan (Universitas Katolik Widya Karya Malang, 2023)
Dementia is a cognitive decline that is so severe that it interferes with activities of daily living and social activities. Cognitive decline in dementia usually begins with a decline in memory or memory (forgetfulness). Cognitive function is the main human capital in the activities of daily life. Brain gymnastics is a light exercise that is carried out with cross movements in order to harmonize and optimize the performance of the right and left brain so that it can improve cognitive function. This study aims to determine the results of the application of brain exercise on cognitive function in the elderly with dementia. Quantitative research with a cross sectional approach and sampling collection technique with purposive sampling with a sample of 34 respondents. The data collection tool used was the Mini Mental Status Examination (MMSE) questionnaire. It was found from this study that before brain exercise, normal cognitive function was 0, while moderate was 2 respondents (5.9%) and mild cognitive function was 32 respondents (94.1%). After brain exercise, normal cognitive function was 14 respondents (41.2%) while 20 respondents (58.8%) had moderate cognitive function and 0. mild cognitive function.